About the Terms “Borrowing”, “Phraseological Borrowing” - Mavlonova Nargiza Alisherovna (Researchparks Publishing, 2023)
The present article offers the multilevel nature of the English-Russian-Uzbek phraseological movements of various levels of the structure of the language, which are examined using examples.